Tyrosine replacement in P-selectin glycoprotein ligand-1 affects distinct kinetic and mechanical properties of bonds with P- and L-selectin - Ramachandran, Vishwanath (National Academy of Sciences, 1999)
Selectins are adhesion molecules that initiate tethering and rolling of leukocytes on the vessel wall. Rolling requires rapid formation and breakage of selectin–ligand bonds that must have mechanical strength to resist premature dissociation by the forces applied in shear flow. P- and L-selectin bind to the N-terminal region of P-selectin glycoprotein ligand-1 (PSGL-1), a mucin on leukocytes. To define determinants on PSGL-1 that contribute to the kinetic and mechanical properties of bonds with selectins, we compared rolling of transfected preB cells expressing P- or L-selectin on transfected cell monolayers expressing wild-type PSGL-1 or PSGL-1 constructs with substitutions in targeted N-terminal residues. Rolling through P- or L-selectin required a Thr or Ser at a specific position on PSGL-1, the attachment site for an essential O-glycan, but required only one of three nearby Tyr residues, which are sites for Tyr-SO(3) formation. The adhesive strengths and numbers of cells rolling through P- or L-selectin were similar on wild-type PSGL-1 and on each of the three PSGL-1 constructs containing only a single Tyr. However, the cells rolled more irregularly on the single-Tyr forms of PSGL-1. Analysis of the lifetimes of transient tethers on limiting densities of PSGL-1 revealed that L-selectin dissociated faster from single-Tyr than wild-type PSGL-1 at all shears examined. In sharp contrast, P-selectin dissociated faster from single-Tyr than wild-type PSGL-1 at higher shear but not at lower shear. Thus, tyrosine replacements in PSGL-1 affect distinct kinetic and mechanical properties of bonds with P- and L-selectin.